Algorithm for the Management of Intracranial Hypertension in Children with Syndromic Craniosynostosis. Issue 2 (August 2015) - Spruijt, Bart; Joosten, Koen F. M.; Driessen, Caroline; Rizopoulos, Dimitris; Naus, Nicole C.; van der Schroeff, Marc P.; Wolvius, Eppo B.; van Veelen, Marie-Lise C.; Tasker, Robert C.; Mathijssen, Irene M. J.
<x xml:space="preserve">Abstract</x> Background: The purpose of this study was to examine the relationship of head growth, obstructive sleep apnea, and intracranial hypertension in patients with syndromic or complex craniosynostosis, and to evaluate the authors' standardized treatment protocol for the management of intracranial hypertension in these patients. Methods: The authors conducted a prospective observational cohort study of patients with syndromic craniosynostosis at a national referral center, treated according to a standardized protocol. Measurements included occipitofrontal head circumference, with growth arrest defined as downward deflection in occipitofrontal head circumference trajectory greater than or equal to a 0.5 SD fall from baseline over 2 years, or lack of change in occipitofrontal head circumference growth curve; sleep studies, with results dichotomized into no/mild versus moderate/severe obstructive sleep apnea; and funduscopy to indicate papilledema, supplemented by optical coherence tomography and/or intracranial pressure monitoring to identify intracranial hypertension. Results: The authors included 62 patients, of whom 21 (33.9 percent) had intracranial hypertension, 39 (62.9 percent) had obstructive sleep apnea, and 20 (32.3 percent) had occipitofrontal head circumference growth arrest during the study. Age at which intracranial hypertension first occurred was 2.0 years (range, 0.4 to 6.0 years). Preoperatively, 13 patients (21.0 percent) had intracranial hypertension, which was associated only with moderate/severe obstructive sleep apnea (p = 0.012). In the first year after surgery, intracranial hypertension was particularly related to occipitofrontal head circumference growth arrest (p = 0.006). Beyond 1 year after surgery, intracranial hypertension was associated with a combination of occipitofrontal head circumference growth arrest (p < 0.001) and moderate/severe obstructive sleep apnea (p = 0.007). Conclusions: Children with syndromic craniosynostosis are at risk of intracranial hypertension. The major determinant of this after vault expansion is impaired head growth, which may occur at varying ages. The presence of moderate/severe obstructive sleep apnea also significantly increases the risk of intracranial hypertension. CLINICIAL QUESTION/LEVEL OF EVIDENCE: Risk, III.